Beyond the Conventional Wisdom: A Reply to Sher & Sher (1994) - David Godden (Journal of Research in Rural Education, 1995)
Sher and Sher (1994) criticised the lack ofan Australian rural development policy and, in turn, devised a policy tofill this apparent void. The proffered policy is defective because the analysis on which it is based is generally unsubstantiated, the supporting arguments are frequently invalid, the richness ofAustralian society is generally ignored, and the economic arguments are flawed. The policy prescriptions derived are often as relevant for urban as for rural Australia. By emphasising the indispensability of a uniquely rural policy in Australia, the authors-ironically-may be supporting a prescription that is to the long-run detriment ofrural Australians.